The effect of information cues on sensory evaluations of hard seltzer: low-calorie versus natural flavor - Nayeong Kim; Jaehee Son; Junghoon Moon (Cogent Food & Agriculture)
This study examines how natural flavor and low-calorie information cues affect consumers’ evaluations of sensory attributes, product personality, and satisfaction related to hard seltzer. Using a three-group between-subject design, participants (N = 121) were randomly assigned to no cues (control, n = 39), natural flavor cues (n = 41), or low-calorie cues (n = 41). The natural flavor group perceived hard seltzer as less alcoholic, less sweet, and less carbonated than the control group. In terms of product personality, the natural flavor group characterized hard seltzer as more sincere but less exciting as compared to the findings in the control group. The participants exposed to the low-calorie cues perceived hard seltzer as less sweet than the participants not exposed to these cues. These findings provide valuable insights for manufacturers to enhance their product offerings and for marketers and restaurant managers to enhance their communication in presenting hard seltzer to consumers.